Aging Regulated Through a Stability Model of Insulin/Insulin Growth Factor Receptor Function - Tatar, Marc (Frontiers in Endocrinology, 2021)
Mutations of the insulin-like receptor in Drosophila extend lifespan. New research suggests this receptor operates in two modes. The first extends lifespan while slowing reproduction and reducing growth. The second strongly extends lifespan without impairing growth or reproduction; it confers longevity assurance. The mutation that confers longevity assurance resides in the kinase insert domain, which contains a potential SH2 binding site for substrate proteins. We apply a recent model for the function of receptor tyrosine kinases to propose how insulin receptor structure can modulate aging. This concept hypothesizes that strong insulin-like ligands promote phosphorylation of high threshold substrate binding sites to robustly induce reproduction, which impairs survival as a consequence of trade-offs. Lower levels of receptor stimulation provide less kinase dimer stability, which reduces reproduction and extends lifespan by avoiding reproductive costs. Conditions that induce diapause fully repress insulin receptor stability, block the phosphorylation of low threshold substrates and thus induces a unique molecular program that confers longevity assurance. Mutations of the insulin receptor that block low-phosphorylation site interactions, such as within the kinase insert domain, can extend lifespan while maintaining overall dimer stability. These flies are long-lived while maintaining reproduction and growth. The kinase insert domain of Drosophila provides a novel avenue from which to seek signaling of the insulin/insulin like growth factor system of humans that modulate aging without impacting reproduction and growth, or incurring insulin resistance pathology.